Genesis and Classification of Some Tea-growing Soils of Assam - Abhishek Das; Nayan Ahmed; Prasenjit Ray; S.K. Ray; T.J. Purakayastha; Sunanda Biswas; Ranjan Bhattacharyya; K.K. Bandyopadhyay (Journal of the Indian Society of Soil Science, 2023)
A study was conducted to ascertain the major pedogenic processes occurring in the tea growing soils of Assam. Seven representative pedons from three different tea estates namely, Kakodonga (P1 and P2), Maheema (P3, P4 and P5) and Jamguri (P6 and P7) of Jorhat and Golaghat districts in Assam were studied. Among the tea estates, Jamguri tea estate has the history of following organic cultivation practices for more than 20 years. The results indicated that the tea growing soils were brown to brownish yellow/ reddish yellow in colour and the texture of which varied from sandy clay loam to clay loam with predominantly sub-angular blocky soil structure. Sand content showed decreasing trend with depth, whereas clay content increased with depth but no such trend was observed for silt content. Relatively higher organic carbon density was observed (considering 100 cm soil depth) in organically grown tea gardens (P6 and P7 profiles) than conventionally grown (inorganic) tea gardens. Electrical conductivity, base saturation and sum of cations decreased with depth. The soils in sub-surface horizons showed patchy clay cutans confirming the presence of argillic horizon and ongoing illuviation process of pedogenesis. The studied tea-growing soils were classified as Typic Hapludults at Subgroup level with Ap-Bw-Bt horizon sequence. The information generated in the study would be useful for effective management of the tea growing soils of Assam.